The The influence of the Dialogic Reading Method with PEER-CROWD Techniques on the Listening and Speaking Skills of Preschool Children: A Quasi-Experimental Study - Surifah, Jamilatus; Rolina , Nelva (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
Listening and speaking skills in children play an important role in their language development. These two skills complement each other and provide a strong foundation for children to interact with the world around them, learn effectively, and build good relationships with others. This study investigated the effect of the dialogic reading method on improving the listening and speaking skills of children aged 4-5. Using a quantitative approach of the quasi-experimental type with a non-equivalent control group design type. The subjects in this study were divided into two classes, namely the experimental and control classes with a total of 34 children in groups A1 and A2 of ABA Kindergarten Perumnas Condongcatur, Depok District, Sleman. In the experimental class there were 17 children, and the control class 17 children. The application of the dialogic reading method was applied during the activity of reading story books together consisting of six to eight children with a duration of about 15-18 minutes. The joint reading activity was carried out 4 times. The story book used for the experimental group has been modified to make it easier to remember the sequence of CROWD questions at the prompt stage. The modification lies in the question assistance stickers that will be asked to the child which are placed on certain pages. The instrument used is an observation instrument for the listening and speaking skills of children aged 4-5 years. The data analysis technique uses the Independent Sample t-Test with a significance level of 0.05. Based on the results of the data analysis, it can be concluded that: (1) There is a significant influence of the dialogic reading method on the listening skills of children aged 4-5 years with the results of the independent t-test obtained a Sig value (2-tailed) of 0.000 <0.05 and a calculated t value of 4.757; (2) There is a significant influence of the dialogic reading method on the speaking skills of children aged 4-5 years with the results of the independent t-test obtained a Sig value (2-tailed) of 0.004 <0.05 and a calculated t value of 3.131. In short, the application of the dialogic reading method has an effect on the listening and speaking skills of children aged 4-5 years.